Peran Guru PAI dalam Pengembangan Toleransi Peserta Didik Melalui Budaya Sekolah di SMA N 8 Yogyakarta - asifa, falasipatul (Universitas Alma Ata, 2018)
In fact that the rapid development of science and technology has eroded the values of tolerance on the students shown by no mutual respect and respect for differences. The role of Islamic Religion Education (PAI) teachers as the heir of moral values and religious teaching of Islam were also supported by school culture into away and expected to be able to develop student tolerance. This research was a qualitative research, with the background SMA N 8 Yogyakarta. Data collection was conducted by observation, interview, and documentation. The result shows that: First, the role of PAI teacher for development tolerance through religious culture in SMA N 8 Yogyakarta was a designer, a movers, an evaluator, and a motivator. Second, the supported factors were adequate facilities and infrastructure such as places of worship and library. Good relationship between principals, teachers and employees, parents and students, and a supportive order. As for the inhibiting factor was the negative impact of science and technology.Keywords: PAI teacher, tolerance, school culture